2021
DOI: 10.3390/jcm11010020
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Single Dose of Betamethasone in Imminent Preterm Labour

Abstract: Background: A complete course of prenatal corticosteroids reduces the possibility of morbimortality and neonatal respiratory distress syndrome (RDS). Occasionally, it is not possible to initiate or complete the maturation regimen, and the preterm neonate is born in a non-tertiary hospital. This study aimed to assess the effects of a single dose of betamethasone within 3 h before delivery on serious outcomes (mortality and serious sequelae) and RDS in preterm neonates born in tertiary vs. non-tertiary hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…Bu çalışmada her üç grup arasında intraventriküler kanama, sepsis ve mortalite açısından anlamlı fark bulunmamıştır (14). Başka bir çalışmada 12 mg betametazonun, hiç antenatal steroid uygulanmayanlara göre RDS'yi azalttığı bulunmuştur (8). Bu çalışmada ayrıca antenatal steroid uygulanan grupta daha az mekanik ventilasyon ihtiyacı, daha düşük toplam solunum desteği ihtiyacı ve daha düşük oksijen desteği ihtiyacı olduğu bulunmuştur.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Bu çalışmada her üç grup arasında intraventriküler kanama, sepsis ve mortalite açısından anlamlı fark bulunmamıştır (14). Başka bir çalışmada 12 mg betametazonun, hiç antenatal steroid uygulanmayanlara göre RDS'yi azalttığı bulunmuştur (8). Bu çalışmada ayrıca antenatal steroid uygulanan grupta daha az mekanik ventilasyon ihtiyacı, daha düşük toplam solunum desteği ihtiyacı ve daha düşük oksijen desteği ihtiyacı olduğu bulunmuştur.…”
Section: Discussionunclassified
“…Aynı çalışmada periventriküler lökomalazi, retinopati ve orta ağır bronkopulmoner displazi sıklığının da tek doz steroid uygulananlarda azaldığı bildirilmiştir. Sonuç olarak, doğumdan önce 3. saate kadar steroid uygulamasının RDS'nin şiddetini azalttığı iddia edilmiştir (8). Tek doz antenatal steroidin etkili olduğunu belirten bu çalışmada hasta sayısının az olması kısıtlılık olarak bildirilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Only a few studies in the literature explored the effects of different dose regimens of antenatal CCS prophylaxis, yielding conflicting results. Studies comparing half course of CCS with no CCS therapy ( 18 20 ), showed that the exposure to an incomplete course of prophylaxis decreases the rate of severe neonatal outcomes, especially at very early gestational weeks (25–27 weeks) and in non-tertiary hospitals ( 18 ). Other observational studies compared the administration of an incomplete CCS course vs. a complete CCS course ( 21 24 ) demonstrating a significant improvement of the neonatal clinical outcome with the half dose exposure.…”
Section: Discussionmentioning
confidence: 99%